Construct validation of a hypnotherapeutic algorithm for children with monosymptomatic bedwetting - Adolfo Rafael Lambert Delgado; Lázaro Ibrahim Romero García; Alberto Erconvaldo Cobián Mena (Centro Provincial de Información de Ciencias Médicas, 2024)
Introduction: Bedwetting is a frequent reason to visit pediatric, infant psychiatry, psychology and family medicine services, with more percentage in 5 years children, followed by 7 and 9 years children, in that order.  Objective: To determine the construct validity of the hypnotherapeutic algorithm for patients with monosymptomatic bedwetting.  Methods:  A complex investigation of 97 patients was carried out, who were assisted in the Therapeutic Hypnosis Clinic of the University of Medical Sciences in Santiago de Cuba, from February, 2021, to July, 2022 which was structured in 3 methodological phases of construct validation to continue the phase IV of hypnotherapeutic algorithm content validation, on the base of 2 quasi-experiments without control group and a quasi-experiment with non equivalent control group of the second phase of this investigation. Results: The factorial analysis on the study of main components was possible, because the factors 1, 2 and 3 should stay, which was expressed in the sedimentation graph and in the explained total variance, through the percentages accumulated in the initial auto values and the sum of saturations to the square of extraction and rotation with 64.24%.  Conclusions: The construct validation of the designed algorithm showed relevancy, given by the suitability of the factorial analysis and the Bartlett test of spherical form.